Eusebius's Christian Library and the Construction of "Hebrews," "Jews," and "Hellenistic Judaism" (Relegere: Studies in Religion and Reception, 2012)
This article approaches the idea of "Judeo-Christianity" at an oblique angle. For scholars of late antiquity, the idea of "Hellenistic Judaism" shares some of the problems that scholars of modernity have identified in "Judeo-Christianity." Each of these terms makes explicit and implicit claims about history; each also uses Judaism to reify a particular understanding of Christianity. This article examines the role of the fourth-century bishop and polymath Eusebius of Caesarea, and his famed library, in the creation of “Hellenistic Judaism.” Eusebius drew a distinction between an ancient "Hebrew" theological tradition and a wider "Judaism." Echoing certain modern constructions of "Judeo-Christianity," Eusebius contended that the "Hebrew-Christian" tradition represented the most universal, civilized, and transcendent form of religion.